Daughter of darkness [compact disc, unabridged] - Andrews, V. C. (Virginia C.) (Andrews, V. C. (Virginia C.). Kindred series., 2010)
One night, with the sound of a young man's scream, high school senior Lorelei discovers that her stern but loving father, who adopted Lorelei and her sisters as infants, is no ordinary man. He has raised his beautiful girls for one purpose: to lure young men into their world of shadows. Like her sisters, Lorelei has been trained in the art of seduction and warned to never fall in love. But when she meets a handsome and charming classmate, she boldly defies her family and follows her heart--even if love is a poison.